1999
DOI: 10.1074/jbc.274.49.34832
|View full text |Cite
|
Sign up to set email alerts
|

Role of Iron and Superoxide for Generation of Hydroxyl Radical, Oxidative DNA Lesions, and Mutagenesis in Escherichia coli

Abstract: We measured the generation of hydroxyl radical (OH ⅐ ) and oxidative DNA lesions in aerobically grown Escherichia coli cells lacking in both superoxide dismutases (SodA SodB) and repressor of iron uptake (Fur) using electroparamagnetic resonance and gas chromatography-mass spectrometry with a selected-ion monitoring method. A specific signal corresponding to OH ⅐ generation and an increase in oxidative DNA lesions such as 7,8-dihydro-8-oxoguanine and 1,2-dihydro-2-oxoadenine were detected in the strain deficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(77 citation statements)
references
References 37 publications
3
73
0
1
Order By: Relevance
“…A misbalance in iron homeostasis is well known to cause DNA damage (Nunoshiba et al, 1999). Therefore, we analyzed the expression of genes encoding plant poly(ADPribose) polymerases (APP and ZAP) and Rad51-like protein (AtRAD51), which might constitute the components of the base excision repair (Babiychuk et al, 1998) and recombination repair pathways (Doutriaux et al, 1998;Ries et al, 2000), respectively.…”
Section: The Classical Fe/s Cluster Biosynthesis Pathway Is Present Imentioning
confidence: 99%
“…A misbalance in iron homeostasis is well known to cause DNA damage (Nunoshiba et al, 1999). Therefore, we analyzed the expression of genes encoding plant poly(ADPribose) polymerases (APP and ZAP) and Rad51-like protein (AtRAD51), which might constitute the components of the base excision repair (Babiychuk et al, 1998) and recombination repair pathways (Doutriaux et al, 1998;Ries et al, 2000), respectively.…”
Section: The Classical Fe/s Cluster Biosynthesis Pathway Is Present Imentioning
confidence: 99%
“…It was recently suggested that a central function of Fur is sequestration of Fe(II). Various phenotypes associated with null mutations in fur have been attributed to a concomitant increase in cellular Fe(II) levels, one being increased mutagenesis (16,17). It has been suggested that, at least in part, the increased mutagene-sis is due to the lack of Fur to sequester the free iron (18).…”
mentioning
confidence: 99%
“…Nunoshiba et al (31) suggest that the increased sensitivity to oxidative stress found in an E. coli fur mutant is due to a 2.5-fold increase in the amount of intracellular iron. This excess iron is thought to participate in Fenton chemistry, catalyzing the formation of damaging hydroxyl radicals in the presence of hydrogen peroxide.…”
Section: Resultsmentioning
confidence: 99%
“…Oxidative stress. E. coli and P. aeruginosa fur mutants have been shown to be more sensitive to oxidative stress, presumably due to an increase in intracellular iron (18,31). In order to test sensitivity to oxidative stress, cultures of wild-type and mutant B. japonicum strains were grown and spread plated, and filters with either sterile, distilled water or 3% H 2 O 2 were added to the plates.…”
Section: Resultsmentioning
confidence: 99%